Custos e benefícios da deserção temporária do cuidado paternal em Thoropa taophora (Anura: Cycloramphidae) - Consolmagno, Rafael Camargo [UNIFESP] (2014)
Parental care increases offspring survival, but may promote a decrease in parental survival and reproductive success. Temporary brood desertion is a strategy that mitigates the costs of parental care at the cost of compromising offspring survival. In this study, we used Thoropa taophora, an anuran species with paternal care that lays eggs on wet stripes on rock cliffs, as a model organism to quantify the costs and benefits of temporary brood desertion. We tested the following hypotheses: (1) temporary broad desertion is higher during the day, especially in sites exposed to sunlight, (2) temporary brood desertion minimizes water loss of brooding males during the day, especially in sites exposed to sunlight, (3) the number of eggs consumed by predators is higher during the day, especially in exposed sites. To test hypothesis (1), we recorded the presence of brooding males on their breeding sites during three days. To test hypothesis (2), we conducted an experiment estimating water loss by exposing agar models (with exactly the same size and shape of an adult male) on the rock cliffs for periods of 3 h, both during the day and at night. To test hypothesis (3), we estimated the natural rates of predation during day and at night, and also conducted an experiment removing brooding males for 48 h. Our results show that temporary brood desertion was higher during the day and on exposed sites. Water loss was higher during the day, and it was positively correlated with temperature and negatively correlated with humidity. Despite the high frequency of daytime desertion, egg predation was lower during the day than at night. In the absence of paternal care, predation was even higher at night, and it was mainly promoted by juvenile and adult conspecifics. In conclusion, daytime desertion of paternal care in T. taophora seems to provide physiological benefits decreasing the water loss of brooding males, and imposes relatively low costs in terms of egg mortality.